PENGARUH REBUSAN DAUN SALAM (SYZIGIUM POLYANTHUM WIGHT WALP) TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI SUNGAI BUNGKAL, KERINCI 2016 - Putri Dafriani (Stikes Syedza Saintika Padang, 2016)
Hypertension is one of the degenerative disease. The incidence of hypertension is increasing every year. various strategies undertaken to reduce morbidity and mortality. one of which is the use of bay leaves. This study aims to look at the effect of bay leaf against the reduction in blood pressure of hypertensive patients. This study is a quasi-experimental study. This study using 20 patients suffering from hypertension. patients were divided into two groups, each with about 10 people. the treatment group were given decoction of leaves 2 times daily for 1 week. Blood pressure was measured every day. bay leaf effect on blood pressure was tested by t-test. The results were obtained that the average pre-test blood pressure in the intervention group that is 161/96 mmHg were kolompok control of 154/95 mmHg. Results Paired t-test obtained by the p-value 0.000 in systolic blood pressure and diastolic in the control group with a mean of 40.00 mmHg in systolic and 20 mmHg in diastolic, whereas the control group the results of Paired t-test was obtained p-value 0678 in 0081 in systolic and diastolic by a mean value of -1000 mmHg in systolic and diastolic 3,000. The conclusions from the results of this research that there is the effect of the water of leaves on blood pressure in hypertensive patients in the intervention group Public Health Center of Sungai Bungkal in Kerinci at 2016 and no significant changes in blood pressure in the control group. We hope health worker can suggest patient to use bay leaf for hypertension.Key Words : Bay Leaf, hypertension, blood pressure